EFEKTIVITAS TUGAS LEMBAGA PENEGAKAN HUKUM TERPADU KOTA PEKANBARU DALAM PEMILIHAN UMUM TAHUN 2014 BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 2012 TENTANG PEMILIHAN UMUM DEWAN PERWAKILAN RAKYAT DEWAN PERWAKILAN DAERAH DAN DEWAN PERWAKILAN RAKYAT DAERAH TAHUN 2 - Mulyadi Ranto Manalu; Mexsasai Indra; Abdul Ghafur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The existence of the Integrated Law Enforcement Center (Gakkumdu) Pekanbaru City in completing the follow criminal offense Election maximum rated yet. So hopefully, there is a coordination of the parties involved in Gakkumdu, namely Bawaslu / Supervisory Committee and the Police and the Prosecutor in the city of Pekanbaru. Based on this understanding, then writing this essay to formulate three formulation of the problem, namely: first, how tasks of Integrated Law Enforcement Agencies in Pekanbaru City Election based on Law No. 8 of 2012 on the Election of the Board of Representatives and Regional Representative Council of the Regional Representatives Council year 2014? Secondly, What are the constraints faced Integrated Law Enforcement Agencies Pekanbaru? Thirdly, what the efforts of Integrated Law Enforcement Agencies Pekanbaru to improve its work in the Election? The research method in this study, first, this kind of research is legal sociological and descriptive. Second, research sites Pekanbaru. Hoarse data sources supported by the primary data, secondary data sources and tertiary data sources. Thirdly, data collection techniques used were interviews, and a review of literature. After the data collected then analyzed qualitatively, then draw conclusions with deduktitf thinking method is to analyze the problems of the general form into special shapes. From the research, there are three fundamental problems that it can be concluded, first, the effectiveness of the Integrated Law Enforcement Center tasks (Gakkumdu) in the Crime Case Management legislative elections in 2014 in the city of Pekanbaru is still not optimal, second, Gakkumdu obstacles in carrying out their duties is the level of understanding diantarannya still less to the laws and regulations governing legislative elections, lack of socialization rules and regulations relating to the implementation of legislative elections and the lack of coordination between the personnel sitting in the Sentra Gakkumdu. Third, efforts to improve its work diantarannya Gakkumdu is to improve understanding are still lacking for legislation governing legislative elections, improving socialization rules and regulations relating to the implementation of legislative elections and improve coordination between the personnel sitting in the Sentra Gakkumdu.Keywords : Task - Gakkumdu - General Elections